Deliberative Inequality : A Text-As-Data Study of Tamil Nadu's Village Assemblies - Parthasarathy, Ramya (World Bank, Washington, DC, 2017)
The resurgence of deliberative institutions in the developing world has prompted a renewed interest in the dynamics of citizen engagement. Using text-as-data methods on an original corpus of village assembly transcripts from rural Tamil Nadu, India, this paper opens the "black box" of deliberation to examine the gendered and status-based patterns of influence. Drawing on normative theories of deliberation, this analysis identifies a set of clear empirical standards for “good” deliberation, based on an individual's ability both to speak and be heard, and uses natural language processing methods to generate these measures. The study first shows that these assemblies are not mere "talking shop" for state officials to bluster and read banal announcements, but rather, provide opportunities for citizens to challenge their elected officials, demand transparency, and provide information about authentic local development needs. Second, the study finds that across multiple measures of deliberative influence, women are at a disadvantage relative to men; women are less likely to speak, set the agenda, and receive a relevant response from state officials. Finally, the paper shows that although quotas for women on village councils have little impact on the likelihood that they speak, they do improve the likelihood that female citizens are heard.